2018
DOI: 10.20944/preprints201805.0435.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D Analysis of Upper Limbs Motion During Rehabilitation Exercises Using the Kinect<sup>TM</sup> Sensor: Development, Laboratory Validation and Clinical Application

Abstract: Optoelectronic devices are gold standard for 3D evaluation in clinics but due to the complexity of such kind of hardware and the lack of access for patients affordable, transportable and easy to use systems must be developed to be largely used in daily clinics. The Kinect TM sensor presents various advantages compared to optoelectronic devices: price, transportability but also some limitations: (in)accuracy of the skeleton detection and tracking as well as the limited amount of available points that make 3D ev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…However, it was shown that using the displacement of wrist relative to trunk appears to be a good approach to evaluate upper limb function during rehabilitation exercises using serious games [ 15 ]. Furthermore, results obtained from Kinect and gold-standard optoelectronic device to assess upper limb functions are significantly correlated [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it was shown that using the displacement of wrist relative to trunk appears to be a good approach to evaluate upper limb function during rehabilitation exercises using serious games [ 15 ]. Furthermore, results obtained from Kinect and gold-standard optoelectronic device to assess upper limb functions are significantly correlated [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Kinect somatosensory device produced by Microsoft Corporation is a 3D somatosensory camera. It also includes real-time dynamic capture, image recognition, microphone input, speech recognition, and community interaction [1]- [3]. The patient does not need to wear any sensor on the body.…”
Section: Introductionmentioning
confidence: 99%